News Coverage in the Iraqi Electronic Press for Internal Crises: (An Analytical Study of Al-Zaman and Al-Sabah Electronic Newspapers for the period from 1/ 3/ 2013 to 31/ 3/ 2013) - Jony, Basim Waheed; Abbas, Huda Fadhil (ALBAHITH ALALAMI, 2013)
The research study focused on the need to clarify the relationship between the Websites of Iraqi Newspapers and their roles in covering the internal crises in Iraq. The selection of Iraqi websites for the newspapers Al-Zaman and Al-Sabah was adopted as one of the most important media with a wide audience; and as a model of hot news and continuous coverage of those sites since 2003 so far. As a result, this necessitated the emergence of new types of methods of editing and writing news stories related to Iraq. Consequently, the enormous and rapidly changing amount of Iraq news, the process of preparing and creating news has become a complex industry as it has gone beyond the normal description of current events. This industry had its own means, methods and philosophy. The news, then, is no longer a description of an immediate event of interest. It is, moreover, a window of view of each opinion to use its trends with or against this party or that one; or for the benefit of this process or that one of what was happening in Iraq. In view of the serious problems posed by this subject, this could negatively affect Iraqi society, which raised questions about the research problem developed by the researchers as follows: What are the objective limits set by the Iraqi electronic press in covering the news? Have political crises been a priority for Iraqi electronic newspapers; or is there a balance with other economic, social, security and other aspects? The research consists of an introduction and three topics and a conclusion. The first section dealt with the theoretical framework. The second section tackled the news coverage of the websites of the internal crises. While the third section responded to the analysis of news coverage in Al-Zaman and Al-Sabah electronic newspapers for internal crises. The conclusion referred to the most important findings reached by the researchers for the results and recommendations through the data of the research